2009
DOI: 10.1080/09541440802421193
|View full text |Cite
|
Sign up to set email alerts
|

Means of communication and sources of information: Two-year-old children's use of pictures as symbols

Abstract: People use pictures for many purposes, but two common functions are to communicate information to others and to extract new information. Previous research has demonstrated that 2-year-old children fail in using pictures as sources of information in search tasks (DeLoache & Burns, 1994). The purpose of this research was to investigate if children this age could, nonetheless, communicate via a picture the location of an object they have observed being hidden and, if so, whether experience with this function can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 20 publications
2
13
4
2
Order By: Relevance
“…While the children in the present study at first found not easy to use images to communicate a real observed situation, with the prior successful experience in the search task theperformance significantly improved. These results are not consistent with a previous study (Peralta & Salsa, 2009) in which with a similar task but using printed pictures on paper children found easier to use the images as a mean of communication than as a source of information.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…While the children in the present study at first found not easy to use images to communicate a real observed situation, with the prior successful experience in the search task theperformance significantly improved. These results are not consistent with a previous study (Peralta & Salsa, 2009) in which with a similar task but using printed pictures on paper children found easier to use the images as a mean of communication than as a source of information.…”
Section: Discussioncontrasting
confidence: 55%
“…under the bed), showed to the child in the image where she hid it and then the child had to find the object in the room based on the information provided by the image: Search task. On the other hand, we adapted the task designed by Peralta (Peralta & DeLoache, 2004;Peralta & Salsa, 2009) where the child had to point/show/indicate in a picture the location where she or he had seen an object being hidden by the experimenter: Indicate task. The tasks consisted of four subtests, in each the toy was hidden in four of five different possible locations (bed, cushions, box, armchair and bedside table).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In sum, research has shown that 3-year-old children succeed when the information concerning the hiding location is provided by a scale model. However, when the same information is provided by a printed or video image, children succeed at 2½ years of age, but not at 2 years of age (DeLoache and Burns, 1994;Troseth and DeLoache, 1998;Schmitt and Anderson, 2002;Peralta and Salsa, 2009).…”
mentioning
confidence: 99%